Efeitos da estimulação cerebral não invasiva na qualidade de vida e atividades de vida diária de pessoas com doença de Parkinson: uma revisão sistemática e meta-análise - Machado, Camila Beatriz da Silva (2021)
Background: Parkinson's disease is the second most common neurodegenerative disease, and its progression negatively influences the quality of life and activities of daily living of patients. This fact requires the search for effective, safe and cost-effective treatments, suitable for clinical practice, based on the symptoms and pathophysiology of the disease. Objectives: To carry out a systematic review and meta-analysis of studies evaluating the effects of non-invasive brain stimulation on quality of life and activities of daily living in people with Parkinson's disease. Method: A systematic search was performed in the Cochrane Library Central Register of Controlled Trials, EMBASE, PubMed, PsycINFO, CINAHL, LILACS, Scopus, Web of Science and Google Scholar databases on April 5, 2021, without date or publication language restriction. Experimental studies investigating the effects of repetitive Transcranial Magnetic Stimulation (rTMS) and/or Transcranial Direct Current Stimulation (tDCS) on the quality of life and/or activities of daily living in people diagnosed with Idiopathic Parkinson's disease were included. according to the criteria of the London Brain Bank. The risk of bias was assessed using the Rob 2.0 scales for clinical trials and the quality of quasi-experimental studies was assessed using the Newcastle-Ottawa scale. Separate meta-analyses were conducted for each of the outcomes of interest, according to the type of intervention, using the Review Manager software (version 5.4.1). A value of P < 0.05 was considered for statistical significance. Results: 17 studies were included in the systematic review and 13 of these were included in the meta-analysis. The results of the meta-analyses indicated a statistically significant effect of rTMS on the activities of daily living of individuals with Parkinson, in the medium term, but no effect of rTMS or tDCS was observed for the quality of life of these patients. Sensitivity analyzes showed no change in the direction of effects for both rTMS and tDCS on the quality of life of individuals with Parkinson's. Conclusion: This systematic review and meta-analysis demonstrated that rTMS is a viable technique for improving activities of daily living in people with Parkinson's disease. The effects of non-invasive brain stimulation on the clinical treatment and quality of life of Parkinson's patients need to be further explored, including an understanding of how different therapy parameters and individual aspects influence outcomes.